Intraoperative Monitoring of External Branch of the Superior Laryngeal Nerve: Functional Identification, Motor Integrity, and its Role on Vocal Cord Function. (2nd November 2018) - Gurleyik, Emin; Gurleyik, Gunay
ABSTRACT: Purpose : Beside recurrent laryngeal nerve (RLN), protection of the external branch of the superior laryngeal nerve (EBSLN) is required for complication-free thyroid surgery. This study investigates the contribution of intraoperative neuromonitoring (IONM) to identification and motor integrity of the EBSLN. Methods : This prospective study was performed on 245 EBSLNs in 147 patients with thyroid surgery. The rate of visual identification, contribution of IONM to functional localization, the rate and levels of recordable waveform amplitude from vocal cord (VC) movement were determined during surgery. Results : 164 (66.9%) EBSLNs were visually identified and additional 74 branches were functionally identified by IONM. Additional identification rate of IONM was 30.2%. Seven (2.9%) EBSLNs could not be identified during surgery. Cricothyroid muscle (CTM) twitch established functional integrity in 97.1% of EBSLNs. Electrophysiological stimulation of 151 (63.4%) EBSLNs created waveform amplitude >100 µV that mean amplitude level was calculated as 186 µV, and an amplitude >300 µV was recorded in 19 of 151 (12.6%) EBSLNs. Conclusions : In addition to visual identification, surgeons can functionally localize the EBSLN with the assistance of IONM that CTM twitch is a reliable evience for functional integrity of the EBSLN. In the majority of patients, stimulation of the EBSLN creates recordable waveform amplitude thus the EBSLN appears to be a second source of motor innervations for intrinsic laryngeal muscles.